Research Progress on Campus Bullying in Primary and Secondary Schools - Yongmei, Hou (Current Progress in Arts and Social Studies Research Vol. 3, 2024)
Background: Campus bullying has become a common social problem and has attracted widespread attention from the Chinese government and various sectors of society in the past decade, but it has not been effectively resolved. The reason behind this is that people (including the general public and academia) have a vague understanding of campus bullying and there are many misunderstandings. Objective: To explore the incidence, characteristics, causes, and risk factors from macro, meso, and micro levels, in order to provide reference opinions for preventing and intervening in campus bullying. Methods: This article searched for relevant literature at home and abroad under the themes of "Middle School Students" AND "Campus Bullying", "Primary School Students" AND "Campus Bullying", selected 70 papers for analysis, presented the incidence and trend of campus bullying, elaborated on the concept, characteristics, hazards, and difficulties in handling campus bullying. Results: The results of this article indicate the following 4 points. First, the incidence rates of Campus Bullying in Primary and Secondary Schools in various regions range from 20.45% to 35.3%, with bullying rates ranging from 8.9% to 45.1% and being bullied rates ranging from 10.7% to 43.4%. Second, the Characteristics of campus bullying in primary and secondary schools are as follows: (1) intentionally done, with significant contrast in strength and weakness; (2) aggressive and highly harmful; (3) concealed places; (4) repeated occurrence and difficulty in obtaining evidence. Third, campus bullying poses a serious threat to the physical and mental health of both the bullies and the victims, especially causing immediate and far-reaching psychological impacts on both parties. Finally, there are many difficulties in the governance of campus bullying, as the influencing factors of campus bullying are extremely complex, including demographics, psychological and behavioral characteristics, lack of family education and insufficient emotional support, mainstream peer alienation, and support from deviant peers, inadequate school supervision and lack of disciplinary power for teachers, and Lack of legal system and lack of disciplinary basis. Conclusion: Campus bullying is a pervasive problem affecting the physical and mental health of students, school management, and societal stability.